Orbitofrontal Cortex Volumes in Patients Diagnosed with Somatic Symptom Disorder - Emir, Burcu Sırlıer; Atmaca, Murad; Kılıçaslan, Aslı Kazğan; Yildiz, Sevler; Yıldırım, Hanefi (My University, 2023)
Aim: Somatic symptom disorder (SSD) is a psychiatric disorder with unknown etiopathogenesis that is still under investigation. The results of neuroimaging studies on SSD have shown that some brain regions may be associated with it. In this connection, this study aims to explore the orbitofrontal cortex (OFC) morphometric changes in patients with SSD to better comprehend the etiopathogenesis.Material and Methods: The study enrolled 20 patients and 20 healthy controls. All study participants were administered a sociodemographic and clinical questionnaire, the Hamilton Depression Rating Scale (HAM-D) and the Hamilton Anxiety Rating Scale (HAM-A). The volumes of total brain, OFC, total white matter, and total gray matter were measured by a magnetic resonance imaging (MRI)-based method in studied patients. Results: Orbitofrontal cortex volume was significantly smaller in the patient group than in healthy controls (p<0.05). No significant difference between the two groups could be observed in total brain, white matter and gray matter volumes (p>0.05).Conclusions: The OFC was markedly smaller in SSD patients than in healthy controls, suggesting that the OFC may be associated with SSD pathophysiology. Future studies examining the functional features of the OFC using imaging and cognitive function tests will likely shed more light on this issue.
Keywords: Volume; MRI; Somatic symptom disorder; orbitofrontal cortex